EXTH-82. T CELL HITCHHIKING AS A MECHANISM OF DRUG DELIVERY TO THE BRAIN. (12th November 2021) - Singh, Kirit; Gedeon, Patrick; Schaller, Teilo; Snyder, David; Khasraw, Mustafa; Sampson, John
Abstract: INTRODUCTION: The blood-brain barrier (BBB) restricts access to the central nervous system (CNS). Our brain bispecific T cell engager (hEGFRvIII:CD3 BRiTE) treats subcutaneous syngeneic tumor (CT2AvIII) but not intracranial CT2AvIII. CD3 engaging molecules such as nanoparticles can be carried into the brain by binding to activated T cells. We therefore sought to determine if co-administration of larger molecules (BRiTE, approx. 55kDa) with activated T cells could cross the BBB, enhancing survival. METHODS: We implanted 8–10-week-old transgenic hCD3 mice (n=7-8 per group) with 30, 000 CT2AvIII cells. Tumors were established for 6 days. Mice were administered either (1) autologous lymphocyte transfer (ALT) alone (single intravenous (IV) injection, 1 x 10 7 activated T cells), (2) serial IV BRiTE doses (50ug, 10 days) (3) BRiTE and ALT or (4) no treatment. Mice were followed for survival using Kaplan-Meier curves and compared via log rank test. Targeted mass spectroscopy analysis as well as PET/CT imaging of mice administered Iodine-124 radiolabelled BRiTE was performed to assess for intracranial accumulation. RESULTS: Mice who received BRiTE and ALT demonstrated significantly enhanced survival compared to controls (median survival 29 vs 21 days, p=0.0135). Mice who received only BRiTE or ALT exhibited median survival comparable to controls (p=0.192, p=0.944 respectively). Mass spectroscopy analysis revealed that mice had a 7-fold increased peak area ratio of BRiTE in the CNS when co-treated with activated T cells compared to BRiTE alone (0.14, 0.02 respectively) while PET/CT imaging demonstrated increased radioactive signal over background localized to coordinates within the brain where tumors were injected. CONCLUSIONS: Giving activated T cells alongside BRiTE allows better access to the intracranial compartment and is required to achieve efficacy in mice with syngeneic orthotopic glioma. Future work will determine the optimal dose and schedule for this approach, as well as defining the precise mechanism by which this occurs.